Sustainability Of ISO 14001 Standards Through An Integration With Lean Principles - A. P., Puvanasvaran; Kerk, Swee Tian; Muhammad, Mohd Razali (Science Publications, 2011)
Lean and EMS are widely appreciated by organisations in improving business efficiency and productivity. The distinct systems have worked towards the enhancement of business capabilities, reduction production costs and meeting ISO standards. The paper analyses these two systems and provides an understanding of how these processes have contributed in improving business efficiencies. Past research studies have revealed that there are wide ranging possibilities and scope of expanding the application potential of these systems to provide even better business models. The primary objective of the paper is to provide a conceptual framework through an effective integration of these two systems for enhanced business efficiency and productivity. The study concludes that an integrated business model can help organisations realize potential benefits and possibilities in the field of business enhancement. In this context, the study explores the possibilities of integration and aims to provide an understanding of the individual systems. The research then goes on to explore the possibilities of integrating the two models to provide an effective approach in achieving organisational efficiency. The research methodology applied in the context of this study involved both primary and secondary research methods in gaining a deeper and practical insight into the issues facing Lean and EMS integration. The findings contributed to the framing of new conceptual framework that combines the benefits of both Lean and EMS principles for enhanced business results.